2009
DOI: 10.1103/physrevlett.103.211101
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Fluctuation Power Near Proton Temperature Anisotropy Instability Thresholds in the Solar Wind

Abstract: The proton temperature anisotropy in the solar wind is known to be constrained by the theoretical thresholds for pressure anisotropy-driven instabilities. Here we use approximately 1 million independent measurements of gyroscale magnetic fluctuations in the solar wind to show for the first time that these fluctuations are enhanced along the temperature anisotropy thresholds of the mirror, proton oblique firehose, and ion cyclotron instabilities. In addition, the measured magnetic compressibility is enhanced at… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

50
544
2

Year Published

2014
2014
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 447 publications
(596 citation statements)
references
References 26 publications
50
544
2
Order By: Relevance
“…Closer to the Sun β ||p is lower, so the allowable range of R p should be larger, but the heating may also be stronger. Statistical studies such as these, drawn from a large ensemble of measurements, are a power tool to identify the relative roles of heating and instabilities in modifying the VDFs (Bale et al 2009). A statistical determination of the effects of instabilities within 0.25 AU requires a large ensemble (at least several million) of solar wind measurements over all conditions near the Sun; since the growth rates of the instabilities are small compared to the ion gyro-frequency time resolution is not a driver; ion and electron temperature anisotropies measured to 20 % accuracy.…”
Section: Heating the Corona And Solar Windmentioning
confidence: 99%
See 1 more Smart Citation
“…Closer to the Sun β ||p is lower, so the allowable range of R p should be larger, but the heating may also be stronger. Statistical studies such as these, drawn from a large ensemble of measurements, are a power tool to identify the relative roles of heating and instabilities in modifying the VDFs (Bale et al 2009). A statistical determination of the effects of instabilities within 0.25 AU requires a large ensemble (at least several million) of solar wind measurements over all conditions near the Sun; since the growth rates of the instabilities are small compared to the ion gyro-frequency time resolution is not a driver; ion and electron temperature anisotropies measured to 20 % accuracy.…”
Section: Heating the Corona And Solar Windmentioning
confidence: 99%
“…Since telemetry rates on SPP are highly constrained, we place sufficient storage within the SWEM to run and archive SPAN observations at their maximum data rates throughout each encounter, and then downloaded high resolution data for regions of interest identified after the encounter and an initial examination of summary observations. Finally, to search for wave-particle interactions at the highest cadences, we employ a direct high speed interface between the SWEAP and FIELDS (Bale et al 2015, this issue) instrument suites. Particle counts are relayed to FIELDS through the interface, and a wave-particle correlator calculates correlations and phase delays between particles and electromagnetic fields.…”
Section: Sweap Science Requirements and Performancementioning
confidence: 99%
“…The magnetosheath temperature anisotropy instability problem was first extended to the solar wind proper and solar corona, by Gary et al (2001a, b). Many subsequent works followed including those by , Kasper et al (2003Kasper et al ( , 2008, Marsch et al (2004Marsch et al ( , 2006, , , Matteini et al (2007Matteini et al ( , 2012, Bale et al (2009), Bourouaine et al (2010, Maruca et al (2011Maruca et al ( , 2012, Osman et al (2011Osman et al ( , 2012Osman et al ( , 2013, Marsch (2012), , Adrian et al (2016), and others that the present review might have missed. These works further investigated the effects of temperature anisotropy instabilities in the solar wind by analyzing data obtained from an armada of spacecraft including Helios, Ulysses, WIND, ACE, Stereo, etc.…”
Section: Introductionmentioning
confidence: 99%
“…1, the proton data distribution obtained near 1 AU, in ðb ki ; T ?i =T ki Þ parameter space. Figure 1 is adopted from the paper by Michno et al (2014), where perpendicular and parallel temperatures as well as the density and magnetic field intensity in the solar wind are calculated using data from WIND SWE and MFI instruments (through the SPDF CDAWeb service) (Bale et al 2009;Ogilvie et al 1995;Lepping et al 1995). We then constructed the proton temperature ratio and the parallel plasma beta.…”
Section: Introductionmentioning
confidence: 99%
“…Schekochihin & Cowley 2006;Kunz et al 2012;Santos-Lima et al 2014Berlock & Pessah 2015) and solar wind (e.g. Bale et al 2009) plasmas have demonstrated that instabilities due to anisotropic effects can have a large influence on dynamics.…”
Section: Introductionmentioning
confidence: 99%